NURSING HANDOVER INFLUENCES ON SAFETY OF PATIENT CARE - Awuah-Baffour, Kwadwo (Acta Scientiae et Intellectus, 2024)
Handoffs are a common occurrence in the hospital setting. They are an opportunity for the exchange of information between clinicians and nurses. During this time, nurses need to transfer complete and accurate information. This literature review examines various research papers about handoffs and patient safety. Research shows that ineffective communication during handovers contributes to patient harm. Consequently, nurses need to pay keen attention to multiple details during this process to ensure patient safety. Various research shows that standardized communication tools and bedside handoffs help to improve patient safety during handover. Some of the tools used during handover include the Situation Background Assessment and Recommendation (SBAR) communication tool. The use of these strategies showed improved patient safety metrics and several self-reported advantages by the nurses.